Ikonografi Simbol-simbol Dewi Durga di Kuil Dewi Durga MAA Kecamatan Karawaci, Kota Tangerang - Muria Khusnun Nisa; Syaiful Azmi (Inklusiva: Jurnal Studi Agama-Agama, 2023)
This study will explain the iconography of the symbols of Dewi Durga at the Dewi Durga Temple MAA Tangerang. Researchers are interested in discussing the symbols of Dewi Durga because Dewi Durga is a symbol of the “mother of the universe” which has many manifestations. This study aims to discuss the iconography of the symbols of Dewi Durga at the Dewi Durga MAA Temple, Karawaci District, Tangerang City. This study uses a qualitative approach and data processing uses a descriptive-analytical method. The approach used is anthropology by using the theory of symbols put forward by Mircea Eliade. The results and discussion of this study indicate that there is an iconography of the symbols of Dewi Durga at the Dewi Durga MAA Temple such as the weapons used, namely cakra, pedang (khadga), gada, sankha, danus and sara, trisula and padma. Then one hand with the other in abhaya mudra. Worship of Dewi Durga is called Navratri (nine nights). Worship of Dewi Durga is focused on the first to third day. On the fourth to sixth day for Dewi Laksmi and on the seventh to ninth day, people usually worship Dewi Saraswati. On the tenth day, the people celebrate the highlight of the event (Vijaya Dashami). This research concludes that the symbols of Dewi Durga need to be known, especially for adherents of Hinduism. Symbols are the way to go to the sacred and transcendent. Therefore, it is important to know the symbols and meanings contained in them so that worship becomes khusyuk.